2021
DOI: 10.1007/s11146-021-09823-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Households’ Dwelling Valuations, Housing Demand and Mortgage Decisions: Israeli Case

Abstract: Housing policy, as well as academic research, are increasingly concerned with the role of bias in subjective dwelling valuations as a proximate measure of households’ house price expectations and their relationship with housing demand. This paper contributes to this area of study by exploring the possibility of simultaneous relationships between households’ price expectations and incentive to maximise the size of housing services demanded also accounting for the supply side factors and regional perspective. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 125 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Mortgage finance is one of the primary sources of financing the acquisition of residential properties in South Africa. An increase in access to credit increases the demand for properties, and when demand increases, so do the prices holding the supply of residential properties constant (Favara and Imbs, 2015; Koblyakova et al , 2021). The study has further shown that an appreciation in the rand’s value negatively impacts residential property prices.…”
Section: Results Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Mortgage finance is one of the primary sources of financing the acquisition of residential properties in South Africa. An increase in access to credit increases the demand for properties, and when demand increases, so do the prices holding the supply of residential properties constant (Favara and Imbs, 2015; Koblyakova et al , 2021). The study has further shown that an appreciation in the rand’s value negatively impacts residential property prices.…”
Section: Results Of the Studymentioning
confidence: 99%
“…Despite long and vast literature on monetary policy on house prices, there is a growing consensus that central banks’ influence on monetary policy has contributed significantly to the residential property prices fluctuations. The boom and bust of house prices were attributed to changes in several monetary policy proxies such as interest rates (Baily et al , 2008; Dullien et al , 2008; Dieckelmann et al , 2023; Jordà et al , 2015; Shi et al , 2014), conditions of obtaining mortgage finance, (Karley, 2006; Koblyakova et al , 2021) and other factors such as economic growth (Agnello and Sousa, 2009; Khan et al , 2014; Yildirim and Yağcibaşi, 2019). The study discussed literature with regard to the impact on interest rates on house prices, the impact of mortgage finance on residential property prices and finally, the impact of other monetary policy factors such as economic growth, inflation, inflation and exchange rate.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Una de las variables que aporta de manera positiva al modelo es la edad, debido a que es importante destacar la capacidad de experiencia y de negociación en la adquisición de viviendas, con un incremento de 1.33%, por eso Koblyakova et al (2021) indican que en su estudio la edad afecta de manera positiva y bajo esto los hogares tienden a controlar la demanda de viviendas. Por eso los jefes de hogar en cuanto a edad bordean por los 46 años quienes tienden a destacar más en la tenencia de viviendas.…”
Section: Discussionunclassified
“…The scientific literature on the real estate market focuses mainly on the analysis of housing demand and supply (Elder & Zumpano, 1991;Kenny, 1999;Börsch-Supan et al, 2001;Fingleton, 2008;Davidoff, 2013;Glaeser & Gyourko, 2018;Koblyakova et al, 2022). Researchers using econometric models try to forecast the forces of supply and demand to illustrate the directions of the real estate market.…”
Section: Literature Reviewmentioning
confidence: 99%